Debt market trends and predictors of specialization: An analysis of Pakistani corporate sector - Kanwal Iqbal Khan; Faisal Qadeer; Mário Nuno Mata; Rui Miguel Dantas; Jo\~ao Xavier Rita; Jéssica Nunes Martins (Journal of Risk and Financial Management, 2021)
Recently, debt structure research has started focusing on the strategic perspective of financing choices, particularly to understand the reasons for debt specialization (DS). This paper examines trends of specialization over time and industry by using a comprehensive dataset on types of debt employed by the public limited companies during 2009-2018. The objective of the current study is to analyze the effect of debt market conditions by identifying significant predictors of DS. Time-series and cross-sectional results confirm the existence of DS, which is further validated by the findings of the cluster analysis. The empirical results indicate that overall, 61% of the companies solely rely on a single type of debt, mostly on short-term obligations accompanied by long-term secured and other debts. Moreover, small, mature, rated, group-affiliated, and low-leverage companies incline more towards this strategy. Credit rating, debt maturity, financial and interest coverage ratios serve as the primary determinants of the debt market that are significantly associated with the measures of DS. The results contribute to the capital structure literature by specifying that financing choice has an important implication in deciding the debt structure composition of the organizations.
Keywords: 330; capital structure; debt market conditions; debt specialization; debt structure; financial instruments; financing choices; long-term loans; short-term loans